Technology Treaties and Climate Change - Hans Gersbach; Marie-Catherine Riekhof (ETH Zurich, CER-ETH - Center of Economic Research, 2017)
We introduce an international technology treaty that couples the funding of research for a more advanced abatement technology with an international emissions permit market. Under the treaty, each country decides on the amount of permits for its domestic industries, but a fraction of these permits is auctioned on the permit market, and the revenues are used to scale up license revenues for the innovators of abatement technologies. We discuss the conditions under which such a technology treaty can slow down climate change through technological innovations and whether it creates complementary incentives for countries to tighten permit issuance. Finally, we discuss how participation in Tech Treaties can be fostered and how such treaties might be implemented.
Keywords: H23; Q54; O31; 330; Climate change mitigation; Technology promotion; International permit markets; International treaty; Externalities; Klimawandel; Klimapolitik; Technologiewahl; Externer Effekt; EU-Emissionshandel; Innovation; EU-Staaten